VD_FINDINFO Arrêt / 2009 / 640 vom 24. August 2009 - VD Tribunal cantonal (2009)
DÉPENS, FRAIS JUDICIAIRES, DÉCISION SUR FRAIS, PREMIÈRE INSTANCE, PROCÉDURE CANTONALE | 49 al. 1 LPA-VD, 52 LPA-VD, 56 al. 3 LPA-VD